FORMATION OF CRITICAL THINKING OF FUTURE MATHEMATICS TEACHERS BY MEANS OF GEOMETRY - Proshkin, Vladimir; Astafieva, Maria; Radchenko, Svetlana (Educological discourse, 2018)
The essence of the concept of critical thinking as a modern pedagogical phenomenon is disclosed in the article. It is revealed that among the most important competencies, which are relevant to the work of a modern teacher, teachers often refer to critical thinking as the ability to critically process various information, the ability to produce ideas, identify strategic issues and solve them, find convincing arguments, take responsibility, defend your position and correct it under the reasonable influence of the opponents. The theoretical foundations of the process of formation of critical thinking of future teachers in the process of professional training at the level of principles, properties, methods, stages are identified. The analysis of the project "The Higher Education Standard of Ukraine" in the field of knowledge 01 "Education" for specialty 014 "Secondary Education", subject specialization 014.04 "Secondary Education (Mathematics)", which provides for the formation of a number of competencies among students is carried out. It is found that the basis of the above listed competencies and learning outcomes is critical thinking. It is proved that geometry (in particular, constructive and projective), its methods and tasks have inexhaustible possibilities and means that can be used as an effective tool for critical thinking formation in the process of professional training of future mathematics teachers. For an example, we solve two problems of Euclidean geometry (a construction task and a proof) with the use of the Desargues theorem- one of the key statements of projective geometry.